Risk factors and Occurrence of Small vessel disease in Acute sensorineural hearing Loss In the Elderly: protocol for a multicentre cross-sectional study - Oussoren, Fieke K.; van Leeuwen, Roeland B.; Schermer, Tjard R.; Hensen, Erik F.; Lammers, Marc J. W.; Poulsen, Louise M. N.; Kardux, Joost J.; Colijn, Carla; Bruintjes, Tjasse D. (BMJ open, 2025)
IntroductionThe aetiology of sudden sensorineural hearing loss (SSNHL) is not certain in a significant number of cases. In 8%–31% of posterior fossa infarctions, acute hearing or vestibular loss precedes neurological symptoms. Also, several retrospective cohort analyses have indicated a higher chance of experiencing a stroke after SSNHL compared with the general population. This higher incidence of stroke suggests vascular involvement in the pathophysiology of SSNHL. The aim of this study is to evaluate the association of cardiovascular disease and idiopathic SSNHL (iSSNHL) by investigating the presence of cardiovascular risk factors and cerebral small vessel disease (CSVD), in patients with iSSNHL and compare this to controls.Method and analysisIn this multicentre cross-sectional study, the ROSALIE study, 205 patients aged 50 years or higher diagnosed with iSSNHL, and 205 controls who are either suspected of trigeminus neuralgia, hemifacial spasm, vestibular paroxysmia or have a cerebellopontine angle neoplasm will be included. The primary outcome is the difference in CSVD, measured by the degree of white matter hyperintensities according to the Fazekas scale and the presence of brain infarctions on MRI, between patients with iSSNHL and controls. The secondary outcome is the difference in prevalence of the cardiovascular risk factors: hypertension, hypercholesterolaemia, smoking status, body mass index and cardiovascular comorbidities; diabetes, stroke and myocardial infarction, between both cohorts.Ethics and disseminationEthics approval has been obtained by the institutional review boards of all participating hospitals. The Medical Research Involving Human Subjects Act does not apply to this study, as has been declared by the regional review board at Leiden University Hospital, registration number 22-3060.Patients will receive the standard diagnostic protocol for iSSNHL in the Netherlands, which consists of pure tone audiometric assessment before and after treatment with corticosteroids and an MRI of the cerebellopontine angle displaying the entire cerebrum. The data will not be available publicly but might be shared on a reasonable request.